(* Title: HOL/Isar_examples/MultisetOrder.thy
ID: $Id$
Author: Markus Wenzel
Wellfoundedness proof for the multiset order.
*)
header {* Wellfoundedness of multiset ordering *};
theory MultisetOrder = Multiset:;
text_raw {*
\footnote{Original tactic script by Tobias Nipkow (see
\url{http://isabelle.in.tum.de/library/HOL/Induct/Multiset.html}),
based on a pen-and-paper proof due to Wilfried Buchholz.}
*};
subsection {* A technical lemma *};
lemma less_add: "(N, M0 + {#a#}) : mult1 r ==>
(EX M. (M, M0) : mult1 r & N = M + {#a#}) |
(EX K. (ALL b. elem K b --> (b, a) : r) & N = M0 + K)"
(concl is "?case1 (mult1 r) | ?case2");
proof (unfold mult1_def);
let ?r = "\<lambda>K a. ALL b. elem K b --> (b, a) : r";
let ?R = "\<lambda>N M. EX a M0 K. M = M0 + {#a#} & N = M0 + K & ?r K a";
let ?case1 = "?case1 {(N, M). ?R N M}";
assume "(N, M0 + {#a#}) : {(N, M). ?R N M}";
hence "EX a' M0' K.
M0 + {#a#} = M0' + {#a'#} & N = M0' + K & ?r K a'"; by simp;
thus "?case1 | ?case2";
proof (elim exE conjE);
fix a' M0' K;
assume N: "N = M0' + K" and r: "?r K a'";
assume "M0 + {#a#} = M0' + {#a'#}";
hence "M0 = M0' & a = a' |
(EX K'. M0 = K' + {#a'#} & M0' = K' + {#a#})";
by (simp only: add_eq_conv_ex);
thus ?thesis;
proof (elim disjE conjE exE);
assume "M0 = M0'" "a = a'";
with N r; have "?r K a & N = M0 + K"; by simp;
hence ?case2; ..; thus ?thesis; ..;
next;
fix K';
assume "M0' = K' + {#a#}";
with N; have n: "N = K' + K + {#a#}"; by (simp add: union_ac);
assume "M0 = K' + {#a'#}";
with r; have "?R (K' + K) M0"; by blast;
with n; have ?case1; by simp; thus ?thesis; ..;
qed;
qed;
qed;
subsection {* The key property *};
lemma all_accessible: "wf r ==> ALL M. M : acc (mult1 r)";
proof;
let ?R = "mult1 r";
let ?W = "acc ?R";
{{;
fix M M0 a;
assume M0: "M0 : ?W"
and wf_hyp: "ALL b. (b, a) : r --> (ALL M:?W. M + {#b#} : ?W)"
and acc_hyp: "ALL M. (M, M0) : ?R --> M + {#a#} : ?W";
have "M0 + {#a#} : ?W";
proof (rule accI [of "M0 + {#a#}"]);
fix N;
assume "(N, M0 + {#a#}) : ?R";
hence "((EX M. (M, M0) : ?R & N = M + {#a#}) |
(EX K. (ALL b. elem K b --> (b, a) : r) & N = M0 + K))";
by (rule less_add);
thus "N : ?W";
proof (elim exE disjE conjE);
fix M; assume "(M, M0) : ?R" and N: "N = M + {#a#}";
from acc_hyp; have "(M, M0) : ?R --> M + {#a#} : ?W"; ..;
hence "M + {#a#} : ?W"; ..;
thus "N : ?W"; by (simp only: N);
next;
fix K;
assume N: "N = M0 + K";
assume "ALL b. elem K b --> (b, a) : r";
have "?this --> M0 + K : ?W" (is "?P K");
proof (induct K rule: multiset_induct);
from M0; have "M0 + {#} : ?W"; by simp;
thus "?P {#}"; ..;
fix K x; assume hyp: "?P K";
show "?P (K + {#x#})";
proof;
assume a: "ALL b. elem (K + {#x#}) b --> (b, a) : r";
hence "(x, a) : r"; by simp;
with wf_hyp; have b: "ALL M:?W. M + {#x#} : ?W"; by blast;
from a hyp; have "M0 + K : ?W"; by simp;
with b; have "(M0 + K) + {#x#} : ?W"; ..;
thus "M0 + (K + {#x#}) : ?W"; by (simp only: union_assoc);
qed;
qed;
hence "M0 + K : ?W"; ..;
thus "N : ?W"; by (simp only: N);
qed;
qed;
}}; note tedious_reasoning = this;
assume wf: "wf r";
fix M;
show "M : ?W";
proof (induct M rule: multiset_induct);
show "{#} : ?W";
proof (rule accI);
fix b; assume "(b, {#}) : ?R";
with not_less_empty; show "b : ?W"; by contradiction;
qed;
fix M a; assume "M : ?W";
from wf; have "ALL M:?W. M + {#a#} : ?W";
proof (rule wf_induct [of r]);
fix a;
assume "ALL b. (b, a) : r --> (ALL M:?W. M + {#b#} : ?W)";
show "ALL M:?W. M + {#a#} : ?W";
proof;
fix M; assume "M : ?W";
thus "M + {#a#} : ?W";
by (rule acc_induct) (rule tedious_reasoning);
qed;
qed;
thus "M + {#a#} : ?W"; ..;
qed;
qed;
subsection {* Main result *};
theorem wf_mult1: "wf r ==> wf (mult1 r)";
by (rule acc_wfI, rule all_accessible);
theorem wf_mult: "wf r ==> wf (mult r)";
by (unfold mult_def, rule wf_trancl, rule wf_mult1);
end;